Premna odorata Blanco against Ascaris spp. Ova Found in Dewormed Swines of Tanauan, Philippines - Pumaras, Rodmie Oliver; Gozon, Shanica Mycah; Osama, Baniaga; Mosquera, Francesca Nicole; Pisarro, Marialo Clarez; Rodrin, Kezia Arielle; Sambrano, Allyssa Loraine (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the effectiveness of Premna odorata Blanco (Alagao) aqueous leaf extract against swine Ascaris spp. ova. Ascaris is a common intestinal parasite in the Philippines, affecting animals and humans. Recent studies have highlighted the increasing antiparasitic resistance among parasites, which has led to the exploration of alternative conventional options and therapeutics to combat parasitic infections effectively. This growing resistance underscores the need for novel treatments, such as plant-based extracts, to address the limitations of current anthelmintic drugs. Researchers aimed to assess the ovicidal activity of the aqueous leaf extract. The study involved collecting Premna odorata Blanco (Alagao) leaves from Cavite City, verifying the plant identity, and preparing various extract concentrations. Swine fecal samples were collected in Tanauan City, Batangas, and examined for Ascaris spp. prevalence and intensity using Modified Kato-Katz. Results showed a moderate infection rate; 15 out of 90 pigs tested positive. Farms 1 and 6 had light infections, suggesting partial effectiveness of previous deworming. Farm 5 showed a high infection even after recent deworming. The Premna odorata Blanco (Alagao) aqueous leaf extract exhibited low efficiency against Ascaris spp. ova, with 15 to 45 minutes exposure times. However, extended exposures of 60 to 120 minutes showed promising results. The 25% extract concentration was ineffective, while 50% and 75% concentrations partially disrupted the eggs. Notably, the 100% concentration successfully penetrated and disrupted the ova. These findings suggested that higher concentrations of Premna odorata Blanco (Alagao) aqueous leaf extract have a better ovicidal effect against Ascaris spp.; however, it requires prolonged exposure. Further research is needed to optimize the extract's use as a potential alternative anthelmintic drug.